STUDENTS’ SATISFACTION WITH HOSTEL FACILITIES IN FEDERAL UNIVERSITY OF TECHNOLOGY, AKURE, NIGERIA - Ajayi, Mary; Nwosu, Akuakanwa; Ajani, Yusuf (European Scientific Journal, ESJ, 2015)
The importance of the social environment in students’ life cannot be overemphasized. Availability, adequacy, and functionality of hostel facilities are the key factors in the determination of students’ satisfaction. Using the hostels in the Federal University of Technology, Akure as a case study, the facilities provided in the hostels were identified and the level of satisfaction with each of the facilities measured using Relative Satisfaction Index. Questionnaires were used in data collection from a total of 322 students taken as the sample size for the study. The study revealed that respondents were dissatisfied with the adequacy and functionality of some facilities such as the laundry, bathroom and toilet facilities due to distance from rooms and the level of cleanliness. The paper recommends the need for provision of more hostels with better designs and current facilities through public-private partnership to meet the needs of the growing students’ population.